2020
DOI: 10.3390/ijerph18010162
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Situational Strength and Burnout: A Multi-Sample Analysis

Abstract: Many studies have examined the effect of situational strength (clarity, consistency, constraints, and consequences) on organisational behaviour, but little has been investigated about its health effects. This study aimed to analyse the relationship between situational strength and burnout. Specifically, we examined whether situational strength characteristics may be associated with burnout, whether these characteristics are risk (or protective) factors for burnout, and whether a strong situation is related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…First, although we did not directly measure patient-care hours or total hours worked, there was a redistribution of total patient-care hours favoring outpatient care and more structured professional time dedicated to scholarly activity and other aspects of professional development. Although reductions in total work hours have not been previously demonstrated to improve burnout, our schedule structure provided more opportunity for other processes previously determined to prevent burnout, including reduced overall clinical constraints . Second, the intervention schedule allowed for more autonomy in selection of activities outside of clinical time, facilitating more longitudinal and personal connections to be made, which has been shown to reduce burnout .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although we did not directly measure patient-care hours or total hours worked, there was a redistribution of total patient-care hours favoring outpatient care and more structured professional time dedicated to scholarly activity and other aspects of professional development. Although reductions in total work hours have not been previously demonstrated to improve burnout, our schedule structure provided more opportunity for other processes previously determined to prevent burnout, including reduced overall clinical constraints . Second, the intervention schedule allowed for more autonomy in selection of activities outside of clinical time, facilitating more longitudinal and personal connections to be made, which has been shown to reduce burnout .…”
Section: Discussionmentioning
confidence: 99%
“…Although reductions in total work hours have not been previously demonstrated to improve burnout, 32 our schedule structure provided more opportunity for other processes previously determined to prevent burnout, including reduced overall clinical constraints. 33 Second, the intervention schedule allowed for more autonomy in selection of activities outside of clinical time, facilitating more longitudinal and personal connections to be made, which has been shown to reduce burnout. 28 Further, the structure increased the interval between rotations with higher rates of moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, the dimensions that have been most frequently used in situational strength studies are constraints, consequences, and clarity (Alaybek et al, 2017;Bowling et al, 2015;Dalal et al, 2020;García-Arroyo et al, 2021;Meyer et al 2009). For example, Meyer et al (2009) used constraints and consequences to analyse the moderating effect of situational strength on the relationship between conscientiousness and performance, finding that both constraints and consequences significantly moderated the conscientiousness-performance relationship being stronger in occupations low in constraints and consequences than in occupations high in constraints and consequences.…”
Section: Situational Strength and Its Dimensionsmentioning
confidence: 99%
“…However, this moderation role of situational strength may vary when actors such as counterproductive behaviours are included in the model. Finally, García-Arroyo et al (2021) analysed the relationship between situational strength and burnout, concluding that situational strength is not only related to behaviour but also to occupational health. Validation of a Scale of Situational Strength at Work…”
Section: Situational Strength and Its Dimensionsmentioning
confidence: 99%
“…These include faulty equipment, incomplete or poor information flow, as well as interruptions by others ( 30 ). Garcia-Arroyo et al ( 31 ) demonstrated that organizational constraints considered from the JD-R perspective should be regarded as demands that can limit autonomy, job control, and decision-making capacity, generating stress, and burnout. Similarly, using JD-R framework, Baka ( 32 ) showed that organizational constraints were associated with job burnout and depression among Polish teachers.…”
Section: Introductionmentioning
confidence: 99%